The Addition of Salmeterol 50 µg Bid to Anticholinergenic Treatment in Patients with COPD: A Randomized Placebo Controlled Trial - Kenneth R Chapman; Peter Arvidsson; AG Chuchalin; DP Dhillon; Peter Faurschou; Roger S Goldstein; AF Kuipers (Canadian Respiratory Journal)
BACKGROUND: In the past, the role of long-acting beta2-agonists in chronic obstructive pulmonary disease (COPD) relative to other agents has been unclear.